D'Arepiz Kitchen / Ahmad Izham Che Daud - Che Daud, Ahmad Izham (2021)
The food industry is a growing industry. If we talk about the development of the world of food industry, there will be no end. Everyone in every different country and county has different tastes and different views on food. This is due to the diversity of cultures and traditions that affect the food industry. However, there are still those who can accept this type of food from abroad because it is similar or tastes close to local food. Our products focus on healthy eating and provide awareness to the community on the importance of healthy eating to daily life. Our target buyers are wives or those who live alone who are tired of cooking at home. The preparation of our products is provided in a clean and conducive environment. I started an online business starting on April 1, 2021 using Facebook social media as a platform for buying and selling. We receive various feedbacks from customers about how good the quality of our products is. We use various marketing techniques to attract customers to buy our products. Teaser, Soft selling, Hard selling is a strategy we use to attract customers to buy with us. We found that the strategy we used work well and received many orders from customers. The tagline we use “Cheap and Definitely Tasty” is trending on Facebook due to the viral power one of our customers.